2004
DOI: 10.1080/1120009x.2004.11782372
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of P27 and Cyclin D1 Co-Expression in Laryngeal Squamous Cell Carcinoma: Possible Target for Novel Therapeutic Strategies

Abstract: Tumour cells are characterised by uncontrolled growth due to alterations in the genes that play a key role in cell repair systems and apoptosis: pro-mitotic oncogenes such as cyclin D1, and tumour suppressor genes such as p27. Recent studies have demonstrated that these genes are involved in different epithelial neoplasms and that their expression is generally associated with prognosis. The aim of this immunohistochemical study was to analyse the clinical relevance of cyclin D1/p27 co-expression in a homogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, a subsequent Phase II study of lapatinib in 42 patients with advanced SCCHN demonstrated no responses and disappointing median PFS (1.6 months), despite modest rates of stable disease (37% in EGFR inhibitor-naive patients, and 20% in the remainder) [86]. There are multiple other targets under investigation, such as cyclin D1 (the expression of which has been shown to correlate with poor prognosis) [87].…”
Section: Targeted Therapymentioning
confidence: 99%
“…However, a subsequent Phase II study of lapatinib in 42 patients with advanced SCCHN demonstrated no responses and disappointing median PFS (1.6 months), despite modest rates of stable disease (37% in EGFR inhibitor-naive patients, and 20% in the remainder) [86]. There are multiple other targets under investigation, such as cyclin D1 (the expression of which has been shown to correlate with poor prognosis) [87].…”
Section: Targeted Therapymentioning
confidence: 99%
“…So far, many research literatures have confirmed that cell cycle regulation get involved in the pathogenesis of laryngeal cancer. For example, overexpression of cyclin-D1 can be used as a marker to predict relapse in patients with LSCC after primary curative resection ( 6 ); circMYLK/miR-195/cyclin D1 regulatory axis could affect the proliferation and cell cycle progression of LSCC cells ( 7 ); in relation to the simultaneous expression of p27 protein and cyclin D1, the patients with a cyclin D1+/p27- phenotype had the poorest disease-free and overall survival rates ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…40,41,44 Clinically, downregulation of p27 has been shown to correlate with poor survival in several types of cancer, [55][56][57] while laryngeal cancer patients with a p27 positive phenotype showed better prognosis. [58][59][60] p21 and p27 have also been shown to play a role in solitary cell dormancy. The effect of p21 and p27 expression on cancer cells in vitro was clarified in studies in which increasing p21 or p27 expression inhibited cell growth and increased the number of cells arrested in the G 1 phase.…”
Section: Molecular Basis For Dormancymentioning
confidence: 99%